2016
DOI: 10.21276/ijlssr.2016.2.4.31
|View full text |Cite
|
Sign up to set email alerts
|

Porcupine, Hystrix indica is in Tiger’s Diet, A Case Study, A Choice of Food or Habit For Survival In Corbett Tiger Reserve, Ramnagar, Uttrakhand, India

Abstract: In dry summer season, the chances of food availability become tough and hard. Prey species moves towards water resources. But tiger have a good and ample quality to survive anywhere with its intelligence and adaptability for survival with environment. To detect the food and feeding behaviour of tiger in this dry month, we had collected the tiger scat for scat analysis. Scat analysis is techniques by which we can reconstruct the tiger's diet with the help of undigested remain on which tiger had prayed. This is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Hayward et al (2006) reported that in Africa common leopards consume porcupines in proportion to their local availability. However, in some cases, porcupines may become important prey of large felids (Kumar 2016), and cubs can be occasionally killed by honey badgers even within their den (Arbon 2019). Furthermore, poaching pressure is generally high for the traditional medicine, for porcupine meat and because it is widely considered as a crop pest.…”
Section: Discussionmentioning
confidence: 99%
“…Hayward et al (2006) reported that in Africa common leopards consume porcupines in proportion to their local availability. However, in some cases, porcupines may become important prey of large felids (Kumar 2016), and cubs can be occasionally killed by honey badgers even within their den (Arbon 2019). Furthermore, poaching pressure is generally high for the traditional medicine, for porcupine meat and because it is widely considered as a crop pest.…”
Section: Discussionmentioning
confidence: 99%